Defensoria Pública e Proteção Social: a judicialização das políticas sociais - Glens, Daniely Maria Vaiano (2017)
The objective of this dissertation is to analyze the actions developed by the Public Attorney Office of the State of São Paulo on the scope of judicialization of social policies in the perspective of the guarantee of rights of social protection of the citizen that uses the service. Initially, we present a brief approximation with the context of the access to Justice in Brazil and the access to rights in France, country where we developed a double Master's degree. After that, we present the history of creation of the Public Attorney Office of the State of São Paulo, its organization and some elements that still raise obstacles to the strengthening of the access to Justice as a free public policy. We approached the conception of Social Justice as a principle of the Public Attorney Office and a brief introduction about the development of Social Protection Systems, highlighting the Brazilian and French conjuncture and the main arguments that found discussions about judicial control of social policies nowadays Lastly, we studied the perception of public attorneys, social workers and psychologists about the relationship betvveen Public Attorney Office and Social Protection, pointing out the social policies most required by the users of the service. We saw the main strategies used by legal operators to face the question. extrajudicial acting, interdisciplinary work, the contribution of Social Service and Psychology, the proposal of a paradigm chance in relation to the traditional hierarchy of the System of Justice. As a conclusion, in a double movement, we highlighted the contradictory forces acting on the institution everyday: from the initiatives of democratization of the System of Justice to the mismatches that drives it away from its founding principles